Robust Flatness Tracking Control for the “DC/DC Buck Converter-DC Motor” System: Renewable Energy-Based Power Supply - Ramón Silva-Ortigoza; Alfredo Roldán-Caballero; Eduardo Hernández-Márquez; José Rafael García-Sánchez; Magdalena Marciano-Melchor; Victor Manuel Hernández-Guzmán; Gilberto Silva-Ortigoza (Complexity)
The design of a robust flatness-based tracking control for the DC/DC Buck converter-DC motor system is developed in this paper. The design of the control considers the dynamics of a renewable energy power source that plays the role of the primary power supply associated with the system. The performance and robustness of the control is verified through simulations via MATLAB-Simulink when abrupt changes in some parameters of the system are taken into account. Also, experiments are performed by using a built prototype of the DC/DC Buck converter-DC motor system, a TDK-Lambda G100-17 programmable DC power supply, MATLAB-Simulink, and the DS1104 board from dSPACE. In this regard, the TDK-Lambda G100-17 is implemented with the aim of emulating photovoltaic panels through the solar array mode for generating the power supply of the system. Thus, both simulations and experiments show the effectiveness of the proposed control scheme.